ANALISIS PERSEPSI STAKEHOLDER DALAM KEBUTUHAN PENDIDIKAN TERINTEGRASI PENCEGAHAN PERILAKU BERISIKO REMAJA - Lela Ayu Rezza Bella; Zahroh Shaluhiyah; Ratih Indraswari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Adolescent risk behaviors include smoking, drinking and risky sexual behavior. The three risk behaviors are interrelated and integrated prevention must be carried out between youth stakeholders (parents, teachers and village heads). This study aims to analyze perceptions of stakeholder needs in integrated education in risky behavior of adolescents. This study uses quantitative qualitative methods. Qualitative research subjects amounted to 12 people consisting of 6 teen informants and 6 parent informants taken by purposive sampling method. The technique of collecting data through in-depth interviews. Quantitative research respondents were adolescent stakeholders totaling 167 respondents consisting of 118 parents / guardians of students, 37 teachers, 12 local leaders taken by the total sampling method. Most experiences, perceptions, attitudes and self efficacy show positive results, but adolescent risk behaviors are still quite high so prevention of integrated risk behavior is needed. Education to prevent risk behavior is education to prevent the impact of risky behavior carried out by methods of socialization (68%), peer discussion (49.1%). In addition, by providing entrepreneurship training, discussions with parties affected by risky behavior, and holding positive activities such as sports. The role that can be done is to make an approach to establish good relations with adolescents, provide supervision, and make regulations. The duration of prevention education is ± 1 hour. The place of implementation adapts to the activities to be carried out. The parties who convey risk behavior prevention education are parents, teachers and local leader besides those who have been affected by risky behavior.